Groundwater Ecotoxicology and Chemistry - Di Marzio, Walter Dario (2024)
Ecotoxicology is the study of the effects and fate of contaminant substances on ecosystems. It aims to determine if there is an ecological risk by comparing the concentration that produces toxic effects with the environmental concentration of these chemicals. Although, René Truhaut was de facto recognized as the originator of this area of study, the pioneering contributions of Jean‐Michel Jouany, Truhaut's assistant, in conceptualizing the discipline and defining its objectives are now fully acknowledged (Di Marzio & Sáenz, 2013; Vasseur et al., 2021). Jouany envisioned ecotoxicology as closely linked to ecology, aiming to understand the influence of stress factors on the relationships between organisms and their habitats. This vision has been realized through a substantial body of ecotoxicological research in marine, freshwater, and terrestrial ecosystems from the poles to the tropics. It is likely that, some 50 years ago, Jouany did not envision that we would be discussing the ecotoxicology of groundwater environments. Groundwater ecosystems are crucial to our planet's health, and ecotoxicological knowledge is needed to ensure the protection of the ecosystems and their functions; however, ecotoxicological knowledge of the subsurface lags far behind that of surface ecosystems.